Effects of Non-Surgical Periodontal Treatment on Reactive Oxygen Metabolites and Glycemic Control in Diabetic Patients with Chronic Periodontitis - Simone Marconcini; Enrica Giammarinaro; Saverio Cosola; Giacomo Oldoini; Annamaria Genovesi; Ugo Covani (MDPI AG, 2021)
Periodontal infection may contribute to poor glycemic control and systemic inflammation in diabetic patients. The aim of the present study is to evaluate the efficacy of non-surgical periodontal treatment in diabetic patients by measuring oxidative stress outcomes. Sixty diabetic patients with periodontitis were enrolled, treated with scaling and full-mouth disinfection, and randomly prescribed chlorhexidine mouthwash, antioxidant mouthwash, or ozone therapy. Reactive oxygen metabolites (ROMs), periodontal parameters, and glycated hemoglobin were measured at baseline and then at 1, 3, and 6 months after. At baseline, all patients presented with pathologic levels of plasmatic ROM (388 ± 21.36 U CARR), higher than the normal population. Probing depth, plaque index, and bleeding on probing values showed significant clinical improvements after treatment, accompanied by significant reductions of plasma ROM levels (p < 0.05). At the 6-month evaluation, the mean ROM relapsed to 332 ± 31.76 U CARR. Glycated hemoglobin decreased significantly (∆ = −0.52 units) after treatment. Both the test groups showed longer-lasting improvements of periodontal parameters. In diabetic patients, periodontal treatment was effective at reducing plasma ROM, which is an indicator of systemic oxidative stress and inflammation. The treatment of periodontal infection might facilitate glycemic control and decrease systemic inflammation.